Virucidal activity of Virkon S on human enterovirus - Chan, Yoke Fun; AbuBakar, Sazaly (Malaysian Medical Association, 2005)
The efficacy of Virkon S, a commercial disinfectant as a virucidal spray against human enterovirus 71 (HEV71), the causative agent of the fatal form of hand, foot and mouth disease was examined. At least one log10 reduction of HEV71 titer was achieved when one spray of Virkon (1 or 2) with ten minutes of contact time was applied. The infectivity was completely lost when four sprays of 1 or 2 Virkon were applied, suggesting that at least four sprays of 1 Virkon to the surface bound HEV71 was necessary to completely inactivate the virus. These findings suggest that Virkon S at the proper concentration is suitable to be used as an effective and easy to use disinfectant against HEV71.